Molecular dynamics analysis of phytochemicals from Ageratina adenophora against COVID-19 main protease (Mpro) and human angiotensin-converting enzyme 2 (ACE2). (March 2021) - Neupane, Netra Prasad; Karn, Abhishek Kumar; Mukeri, Imdad Husen; Pathak, Prateek; Kumar, Praveen; Singh, Samayaditya; Qureshi, Insaf Ahmed; Jha, Tarun; Verma, Amita
Abstract: The outbreak of COVID-19 created unprecedented strain in the healthcare system. Various research revealed that COVID-19 main protease (M pro ) and human angiotensin-converting enzyme 2 (ACE2) are responsible for viral replication and entry into the human body, respectively. Blocking the activity of these enzymes gives a potential therapeutic target for the COVID-19. The objective of the study was to explore phytochemicals from Ageratina adenophora against SARS-CoV-2 through in-silico studies. In this study, 34 phytochemicals of A. adenophora were docked with M pro and ACE2 through AutoDock Tools-1.5.6 and their binding affinity was studied. Phytochemicals with higher affinity have been chosen for further molecular dynamics simulations to determine the stability with target protein. Molecular dynamics simulations were studied on GROMACS 5.1.4 version. Furthermore, 5-β-glucosyl-7-demethoxy-encecalin (5GDE) and 2-oxocadinan-3, 6(11)-dien-12, 7-olide (BODO) were found to be potential blockers with excellent binding affinity with Mpro and ACE2 than their native inhibitors remdesivir and hydroxychloroquine respectively. The drug likeness study and pharmacokinetics of the phytoconstituents present in A. adenophora provide an excellent support for the lead drug discovery against COVID-19. Graphical abstract: Image 1 Highlights: The present study is designed to explore the 34 phytocompounds from Ageratina adenophora against SARS-CoV through in-silico studies. Molecular docking study with M pro and ACE2 showed that phytocompounds from Ageratina adenophora have potential efficiency against COVID-19. MD simulations showed that GDE and BODO were found to be potential blockers with excellent binding affinity than their native inhibitors. The drug likeness study and pharmacokinetics of the phytocompounds provide an excellent support for the lead drug discovery against COVID-19.